Implementation of Anti-Corruption Education of the PKn Subjects in Project Citizen-Based Learning - Abdurohim, Nandang; Abdurrohman, Mumu; Ali, Hapid; Nazar, Reza Fauzi (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to describe the implementation of anti-corruption education through project-based citizen learning on The Citizenship Education (PKn) subjects. The research design uses qualitative research focusing on the case study method at MA of Sunan Rahmat in Garut. The results of this study indicate that the implementation of anti-corruption education has been completed with learning activities to analyze problems related to corrupt behavior in the presentation of panels which consist of several activity sections, namely; Problem analysis, alternative policies, proposing solutions, planning activities. The approach of these activities is aimed at growing students in improving some spirits of good behavior and attitudes (good character) which consist of being honest, caring, disciplined, helping each other, determination, humility, hard work, having social intelligence, and being responsible.